1975
DOI: 10.1136/gut.16.5.347
|View full text |Cite
|
Sign up to set email alerts
|

The effects of premedication drugs on the lower oesophageal high pressure zone and reflux status of rhesus monkeys and man.

Abstract: SUMMARY Thirty-five human volunteers and eight Rhesus monkeys were studied with standard gastrooesophageal manometric techniques and their reflux status was evaluated with a pH probe placed in the lower oesophagus. Morphine sulphate, pethidine hydrochloride, or diazepam was given intravenously until drowsiness was induced.The manometric and pH studies were repeated. All three drugs decreased the lower oesophageal high pressure zone and increased the probability of reflux in both monkeys and man. These findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
0
5

Year Published

1978
1978
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 111 publications
(53 citation statements)
references
References 17 publications
(13 reference statements)
2
46
0
5
Order By: Relevance
“…F. Forster, H. Kohier, K. Ewe, and J. Krieglstein Effect of intravenous diazepam on human lower oesophageal sphincter pressure 67 dictions in their observations and our results. As in our study the dose range applied by Hall et al (1975) (approximately 5 and 10 mg diazepam in a subject weighing 70 kg) did not lower the sphincter pressure but rather increased it, our investigation was extended. In order to assess a possible immediate effect developing within the first few minutes or later than 50 minutes after the injection, which would have been missed in the first study (group I), studies in group II were carried out taking these factors into account.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…F. Forster, H. Kohier, K. Ewe, and J. Krieglstein Effect of intravenous diazepam on human lower oesophageal sphincter pressure 67 dictions in their observations and our results. As in our study the dose range applied by Hall et al (1975) (approximately 5 and 10 mg diazepam in a subject weighing 70 kg) did not lower the sphincter pressure but rather increased it, our investigation was extended. In order to assess a possible immediate effect developing within the first few minutes or later than 50 minutes after the injection, which would have been missed in the first study (group I), studies in group II were carried out taking these factors into account.…”
Section: Discussionmentioning
confidence: 85%
“…According to these studies atropine, morphine sulphate, pethidine hydrochloride, and promethazine reduce and triflupromazine hydrochloride increases lower oesophageal sphincter pressure. The first report on the effect of diazepam on the gastro-oesophageal junction was published by Hall et al (1975) who observed a reduction in sphincter pressures after the administration of 2-5 to 10 mg diazepam intravenously in an uncontrolled study. These results are in contrast to the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations